Pillar bearing an inscription - Temples of India Project Team (Jio Institute, 2024)
On one of the pillars in the mandapa of the Bisaldeo Temple is a short inscription that mentions the name of ‘Jogi Achpantadhaja’ or ‘Yogi Achintyadhvaja'.